Perancangan User Experience Aplikasi Pembelajaran Digital Marketing Instagram untuk UMKM dengan Metode Human-Centered Design - Dani Kurnianto; Ratih Kartika Dewi; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The Covid-19 pandemic has been ongoing since December 2019 and has harmed the community in the economic sector, one of which is MSMEs. The recommendation from the government is that buying and selling transactions are carried out indirectly. Therefore, MSME actors are urged to adapt by promoting their sales via digital, one of which is Instagram. However, of the 64 million MSMEs in Indonesia, only 300 thousand have switched to digital, so many MSMEs do not know how important digital marketing is. Understanding digital marketing is very important to understand the market environment, attract consumer interest, and expand marketing reach. However, it is not uncommon for MSME actors to find it difficult to find information about digital marketing. They need a digital marketing learning application that is interactive and comfortable to use by MSME actors. This research was conducted to design the user experience of the Instagram digital marketing learning application for MSMEs with a Human-Centered Design approach, this method focuses on the user because at every stage of the process it involves the user so that it can produce needs that are by the user and produce high satisfaction and are comfortable to use. The final result of the research is in the form of a prototype, the prototype that has been designed will be evaluated by 20 end-users as MSME actors using the user experience questionnaire method, suggestions, and responses. In user experience testing using the user experience questionnaire method, it scored 1.90 on the attractiveness aspect, 1.59 on the perspicuity aspect, 1.93 on the efficiency aspect, 1.85 on the dependability aspect, 1.90 on the stimulation aspect, and 1.60 on the novelty aspect. In the suggestions and responses, found 4 recommendations for improving the design of the solution that is used to improve the design of the solution to suit user needs.